Dampak Kegiatan Ekstrakurikuler Terhadap Keterampilan Menari Siswa Siswa SMP Negeri 34 Kerinci - Wina Hestilia; Indrayuda Indrayuda (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The purpose of this study describes the impact of extracurricular activities on the dancing skills of SMP Negeri 34 Kerinci students. This type of research is qualitative research with descriptive methods. The object of research is students of SMP Negeri 34 Kerinci. This research instrument is the researcher himself. Data collection techniques are carried out by observation, literature study, interviews and documentation. The steps of analyzing data are collecting data, identifying data, classifying data and drawing conclusions. The results showed that students' lack of confidence when doing dance exercises in extracurricular activities, due to students' fear when the teacher told students to come forward and also difficult to understand the material taught, difficult to capture the movements taught by the teacher. The results of the evaluation of dance extracurricular activities at SMP Negeri 34 Kerinci proved that of the 34 people tested, there were 20 students who got A (Very Good), 10 students got B (Good) and 4 students got C (enough). From the overall evaluation results, the teacher held a meeting with the principal for students who got the highest score (Very Good) to be included to take part in the Kerinci Regency FLS2N next year, and had the opportunity to participate in inter-school competitions such as Exspo and Pensi. This shows that SMP Negeri 34 Kerinci is progressing.